Pemilillan Kebijakan Mengatasi Kemacetan Lalu Lintas Di Kota Bogor (Studi Penerapan Analiti.Cal Hirarchi Process (AHP)) - Soedomo, R. Pramono; Mulyono, Sri; Falatehan, A Faroby (Warta Penelitian Perhubungan, 2010)
This paper is a study to produce a poliCtJ to deal with congestion in the city of Bogar by using ahierarchical analysis approach to obtain a poliCt; priority. The results of this study is the main sourceof congestion in the cihj of Bogar is the number of vehicles that exceed the capacihJ of the offendercau.ses congestion in the cihj of Bogar, is the gJVernment. 17ie main obstacle to congestion in the cihJof Bogar is the rule of law. While the poliCtj priori.hj to address congestion in the city of Bogar is thereduction of urban transportation and/ or replacement modes. This is becau.se tire number of vehiclesfrom year to year is alwm;s increasing.Keywords : analytical hierarcln;, policy priori.ties, the number of vehicles, the perpetratorcau.ses congestion